Implementasi SWOT Strategi Pemasaran Online dan Offline Pada PT Roti Nusantara Prima Cabang Jatiasih, Bekasi - Kus Daru Widayati (Widya Cipta - Jurnal Sekretari dan Manajemen, 2018)
PT Roti Nusantara Prima as one of the companies engaged in the field of food retailing, implement marketing strategies with online systems and offline systems in selling and promoting products so that consumers are interested and want to know more what products are offered. Of the two strategies is which is better and more effective to be done in order that the product produced by the company can be accepted and purchased by the community? This research uses qualitative method and descriptive analysis by using several qualitative methods such as Observation Method that is data collection method with direct observation to PT Roti Nusantara Prima Branch Jatiasih Bekasi activity in conducting its marketing, then interview method. In this study the authors take data marketing at PT Roti Nusantara Prima Branch Jatiasih Bekas during the period 2017. The ease of using online facilities to conduct and develop marketing strategies in the sale of products or services does not mean can ignore offline methods to help marketing strategyy. Evidently, the most successful business is a business that still maintains an offline marketing strategy and execute also online methods simultaneously. Online business can take advantage of traditional "offline" marketing and use both media together can produce better returns. This research period was taken during 2017.